Penyelesaian Sengketa Kewenangan Lembaga Negara Independen di Indonesia - Kelik Iswandi; Nanik Prasetyoningsih (Faculty of Law, Universitas Pattimura, 2020)
Competence dispute which involves independent state organs occur several times in Indonesia has an impact on obstruction of competence. Several cases of competence dispute which involve independent state organ have been submitted to the Constitutional Court but not all have been granted. This study aims to examined the concern of competence dispute which involves independent state organ and factors of independent state organ can fulfill the subjectum litis criteria of SKLN in Constitutional Court. The research method is normative by using primary, secondary, and tertiary legal materials, collected from library research. This research analytical data use the statute approach and case approach. The results of this study indicate that the authority of the Constitutional Court does not specifically regulate state institutions that can be subjectum Litis SKLN in the Constitutional Court, there is a gap accommodated by the Constitutional Court in several decisions.